INTERVENSI PSIKOLOGIS UNTUK MENGATASI BULLYING DI DUSUN TEGAL BEDUG, TAMANSARI, LELEA, INDRAMAYU, JAWA BARAT - Agoes Dariyo; Maria Ivana Putri; Zhillan Faranihaq; Shekinah Glory Panjaitan; Agung Valerama (Jurnal Bakti Masyarakat Indonesia, 2022)
Bullying is behavior that is carried out by a person or group of people with the aim of hurting the heart, feelings, orphysically of another person. Bullying can be done by anyone who causes feelings of resentment, disappointment, orhurt to be felt in the victim of bullying which usually occurs due to appearance and family economic factors. Theperpetrators of bullying that occurred in the hamlets of Tegal Bedug, Tamansari, Lelea, Indramayu, West Java weremostly found in children and the victims of this bullying behavior were also children. In order to overcome theseproblems, psychological intervention ef orts were carried out 7 times meeting sessions for perpetrators and victimsof bullying which aim to provide basic knowledge about the meaning and causes of bullying, as well ascharacteristics and steps to overcome bullying behavior for perpetrators and victims of bullying Participants in thisactivity is a student of SD Negeri 02 Tamansari grade 5-6 aged 11-13 years who is a perpetrator and victim ofbullying behavior. The measuring instrument used to determine the ef ectiveness of the psychological interventionprogram is a questionnaire given before (pre-test) and after the activity (post-test). The results of the psychologicalintervention showed that the perpetrators of bullying were able to provide cognitive understanding and could reducetheir bullying behavior. Victims of bullying are also increasingly assertive in defending themselves, fighting back, orsaying the right thing to the bully. ABSTRAK: Perundungan merupakan perilaku yang dilakukan oleh seseorang atau sekelompok orang dengan tujuan untukmenyakiti hati, perasaan, atau fisik orang lain. Perundungan dapat dilakukan oleh siapa pun yang menyebabkanmunculnya perasaan dendam, kecewa, atau sakit hati pada korban perundungan yang biasanya terjadi dikarenakanpenampilan dan faktor ekonomi keluarga. Pelaku perundungan yang terjadi di dusun Tegal Bedug, Tamansari, Lelea,Indramayu, Jawa Barat banyak ditemukan pada anak-anak dan korban dari perilaku perundungan tersebut pun jugaanak-anak. Ternyata anak-anak yang menjadi pelaku perundungan maupun korban perundungan adalah anak-anakyang orang tuanya meninggalkan dusunnya. Guna untuk mengatasi permasalahan tersebut, maka dilakukan upayaintervensi psikologis 7 kali sesi pertemuan terhadap pelaku maupun korban perundungan yang bertujuan untukmemberikan pengetahuan dasar mengenai pengertian dan sebab perundungan, serta karakteristik danlangkah-langkah mengatasi perilaku perundungan untuk pelaku dan korban perundungan Partisipan dalam kegiatanini merupakan siswa SD Negeri 02 Tamansari kelas 5-6 yang berusia 11-13 tahun yang menjadi pelaku dan korbanperilaku perundungan. Alat ukur yang digunakan untuk mengetahui efektivitas program intervensi psikologis adalahkuesioner yang diberikan sebelum (pre-test) dan sesudah kegiatan (post-test). Hasil intervensi psikologismenunjukkan bahwa pelaku perundungan mampu memberikan pemahaman kognitif dan dapat menurunkan perilakuperundungannya. Korban perundungan juga semakin bersikap asertif untuk membela diri, melawan, ataumengatakan hal yang benar terhadap pelaku perundungan.